THE IMPACT OF AUDITING CHALLENGES IN DETECTING AND PREVENTING FRAUD IN ORGANISATIONS : A CASE STUDY OF RWENZORI BOTTLING COMPANY. - ALINAITWE HARRIET (Uganda Christian University, 2025)
In the contemporary business environment, effective auditing practices are indispensable in the detection and prevention of fraud, which poses a substantial threat to both the financial stability and reputational standing of organisations. This study explores the case of Rwenzori Bottling Company, one of Uganda’s leading beverage manufacturers, to examine how auditing challenges namely the shortage of experienced auditors, weak internal control systems, and limited access to reliable auditing tools undermine the organisation’s ability to safeguard against fraudulent activities. While the adoption of advanced auditing technologies has notably enhanced fraud detection capabilities globally, especially in developed economies, their efficacy in the Ugandan context remains limited by inadequate human resource capacity and infrastructural gaps. Drawing on both global literature and regional insights, this research seeks to assess the current state of auditing within Rwenzori Bottling Company, identifying key shortcomings and proposing strategic recommendations aimed at strengthening audit effectiveness. By fostering a culture of accountability and transparency, the study underscores the importance of harmonising technological innovation with skilled human expertise to uphold corporate governance and financial integrity. The research further outlines the study’s background, objectives, key questions, and scope including its geographical, thematic, and temporal parameters thereby laying a comprehensive foundation for a meaningful inquiry into audit-driven fraud prevention within Uganda’s private sector.